Controlling surface morphology and sensitivity of granular and porous silver films for surface-enhanced Raman scattering, SERS - Sherif Okeil; Jörg J. Schneider (Beilstein Journal of Nanotechnology, 2018)
The design of efficient substrates for surface-enhanced Raman spectroscopy (SERS) for large-scale fabrication at low cost is an important issue in further enhancing the use of SERS for routine chemical analysis. Here, we systematically investigate the effect of different radio frequency (rf) plasmas (argon, hydrogen, nitrogen, air and oxygen plasma) as well as combinations of these plasmas on the surface morphology of thin silver films. It was found that different surface structures and different degrees of surface roughness could be obtained by a systematic variation of the plasma type and condition as well as plasma power and treatment time. The differently roughened silver surfaces act as efficient SERS substrates showing greater enhancement factors compared to as prepared, sputtered, but untreated silver films when using rhodamine B as Raman probe molecule. The obtained roughened silver films were fully characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron (XPS and Auger) and ultraviolet–visible spectroscopy (UV–vis) as well as contact angle measurements. It was found that different morphologies of the roughened Ag films could be obtained under controlled conditions. These silver films show a broad range of tunable SERS enhancement factors ranging from 1.93 × 102 to 2.35 × 105 using rhodamine B as probe molecule. The main factors that control the enhancement are the plasma gas used and the plasma conditions, i.e., pressure, power and treatment time. Altogether this work shows for the first time the effectiveness of a plasma treatment for surface roughening of silver thin films and its profound influence on the interface-controlled SERS enhancement effect. The method can be used for low-cost, large-scale production of SERS substrates.